Dietary Quality Indices and Its Cardiovascular Diseases Risk Factors: A Survey from the Kavar Cohort Study - Dehzad, Mohammad Jafar; Safarpour, Ali Reza; Hejazi, Najmeh; Moghdani, Zahra (Galen Medical Journal, 2022)
Background: Atherosclerosis is known to be a significant reason for cardiovascular diseases (CVDs). Hypertension, dyslipidemia, diabetes, obesity, smoking, physical inactivity, and unhealthy diet are the most important causes of atherosclerosis. This study aimed to determine the relationship between DASH Diet Index, Dietary Inflammatory Index (DII), Mediterranean Diet (MEDI-LITE) Index, and CVDs risk factors. Materials and Methods: Out of 4997 patients, all eligible patients with CVDs (n=264) were chosen as the patient group, and 264 healthy individuals were included in the healthy group. Dietary intake and anthropometric measures were evaluated, including height, weight, hip and waist circumference, blood pressure, and lipid profile. Results: Among the three dietary indices, the DASH diet score was significantly higher in the healthy group than in the patient group (P=0.02). An inverse relationship was found between the DASH Diet Index and waist-to-hip ratio (r=-0.33, P=0.042), Visceral Adiposity Index (VAI; r=-0.16, P=0.044), systolic blood pressure (r=-0.13, P=0.035), triglycerides (r=-0.36, P=0.046), total cholesterol (r=-0.47, P=0.02), and low-density lipoprotein-C (LDL-C) levels (r=-0.09, P=0.03) in the patient group. Additionally, the MEDI-LITE Index was inversely associated with body mass index (BMI; r=-0.12, P=0.04), waist circumference (r=-0.065, P=0.05), triglyceride (r=-0.25, P=0.015), total cholesterol (r=-0.4, P=0.02), LDL-C levels (r=-0.2, P=0.006), and systolic blood pressure (r=-0.122, P=0.005) in the patient group. Also, a significant positive relationship was observed between the DII and BMI in both patients and healthy individuals (r=0.76, P=0.006 vs. r=0.24, P=0.01, respectively) and hip circumference (r=0.638, P=0.035) in the patients group. However, no significant relationship was observed between DII and CVDs risk factors. Conclusion: Patients with higher DASH diet scores had lower waist-to-hip ratio, VAI, total cholesterol, LDL-C, triglycerides, and lower blood pressure. In addition, patients with higher MEDI-LITE scores had lower BMI, waist circumference, triglycerides, total cholesterol, LDL-C, and lower blood pressure, but no correlation was found the healthy group.